RENEWABLE TECHNOLOGY OF ELECTRICAL INSTALLATION OF POLTEKBANG BUILDING - Darmeli Nasution (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
In this research, the discussion on electrical installation of buildings as electrical equipment assemblies in buildings that are related to each other, to meet certain objectives or purposes and has coordinated characteristics, what has been stated in the General Electrical Installation Requirements (PUIL 2000). The purpose and objective of electrical installations is that the operation of electrical installations is carried out properly, to ensure human safety from the danger of electric shock, the safety of electrical installations and their equipment, the safety of buildings and their contents from electric fire, and environmental protection. Things that have been considered trivial by the public, unknowingly have triggered the high number of fire cases. Fire can occur if there are three elements, namely combustible material, oxygen and sparks. Electrical short circuit or (electrical short circuit) which causes a spark of fire against flammable materials, still triggers a high rate of fire.